Pembrolizumab joins the anti-PD-1 armamentarium in the treatment of melanoma. (January 2015) - Hersey, Peter; Gowrishankar, Kavitha
ABSTRACT : Pembrolizumab (MK-3475) is a monoclonal antibody that binds to the PD-1 receptor on T cells and prevents binding to its ligands PD-L1 and PD-L2. Blocking this receptor frees T cells from the inhibitory effects of PD-L1 and allows them to mediate antitumor effects against cancer cells. In a large Phase I study of 411 patients with melanoma, high durable response rates over a range of doses and schedules have been shown with very little toxicity. A Phase III study of pembrolizumab comparing two schedules of administration with the current standard treatment with the anti-CTLA-4 monoclonal antibody is in progress. Combinations with other checkpoint inhibitors as well as other anticancer agents are also being evaluated. Approval of pembrolizumab for the treatment of melanoma is expected.